シュンキ カキ ノ ホッキョク タイリュウケン チュウ ノ タイキ エアロゾル ソセイ ト コンゴウ ジョウタイ ノ クウカン ブンプ - 原, 圭一郎; ハラ, ケイイチロウ; 松木, 篤; マツキ, アツシ; 山形, 定; ヤマガタ, サダム; 岩坂, 泰信; イワサカ, ヤスノブ; 山内, 恭; ヤマノウチ, タカシ; Herber, Andreas; Hara, Keiichiro; et al. (2010)
P(論文) 北極ヘイズが頻繁に出現する春季(3-4月),清浄な大気へ変化する時期(5-6月)の北極対流圏内のエアロゾル粒子の組成とその混合状態の空間分布に関して知見を得るため,日本-ドイツ共同で航空機を用いたエアロゾル観測を2000年3-4月(ASTAR 2000)と2004年5-6月(ASTAR 2004)にスバールバル諸島周辺で実施した.春季には酸性状態の硫酸粒子が主要だったのに対し,夏季に移行する時期(6月)には中性の硫酸塩粒子(おそらく(NH_4)_2SO_4)の割合が増加していた.北極ヘイズ現象下ではススを含む粒子の割合が増加し,その多くは外部混合状態で存在していた.一方,バックグラウンド時(非北極ヘイズ時)には,スス粒子の割合は減少し,多くが硫酸(塩)粒子と内部混合した状態だった.ここでは,海塩粒子変質の鉛直変化や土壌粒子の空間分布についても報告を行う. Airborne aerosol measurements around the Svalbard Archipelago were carried out in March-April, 2000 (ASTAR 2000) and in May-June, 2004 (ASTAR 2004) for better understanding of the spatial distribution of aerosol constituents and their mixing states. Major aerosol particles were sulfate particles in both campaigns. In ASTAR 2000 (spring), acidic sulfate particles (mostly H_2SO_4 droplets) were dominant, whereas the relative abundance of neutralized sulfate particles (probably (NH_4)_2SO_4) increased in the transition period (ASTAR 2004). Under Arctic haze conditions, higher relative abundance of aerosol particles containing soot was observed. Most of the soot collected during the haze was present as "external mixing states". In contrast, soot dominantly existed as "internal mixture" with sulfate particles under the background (non-haze) conditions. In the transition period (June in ASTAR 2004), the relative abundance of aerosol particles containing soot decreased clearly. Vertical features of sea-salt modification and spatial distribution of mineral particles are also reported. departmental bulletin paper